Handbook of Neurological Physical Therapy: Evidence-Based Practice - Raju P Shanmuga; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
The book entitled (3z(BHandbook of Neurological Physical Therapy(3y (Bfollows a simple principle and is easy to implement in a day-to-day practice. The main topics covered in this book are neurological examination, neuroradiology imaging, physical therapy in Bell$1 (Bs palsy, stroke physical therapy, parkinson$1 (Bs disease, spinal cord injury rehabilitation, cerebral palsy, cerebellar ataxia, and orthotics in neurological rehabilitation. The book explains the problem of threatening neurological disability with physical therapy interventions. The book is concise and is clear presentation of the latest scientific facts, models, pictures, illustrations and methods of practice. This book is very informative and will give advance information, resources and practical guidance to undergraduate and postgraduate physical therapy students. Additionally this book will also enrich the knowledge of faculty, nurse practitioners, occupational therapists, physiatrist and assistant physicians.s
Keywords: Physiotherapy; Electronic books